A África e os africanos em livros didáticos de história: entre prescrições e realizações - Ferrari, Alice Rosa de Sena (2016)
This dissertation has as its main purpose the study of Africa and Africans as addressed in notions and concepts presented in the Guide of Textbooks and History collections for the 4th year of Elementary School, which were approved by the National Textbook Program (known as PNLD) 2016. It is inserted in the current discussions about how the Directives of the Law no.10,639/03 are expressed in textbooks analyzed in the PNLD. The overall goal, therefore, is to understand how are presented both Africa and Africans in the notions and contents published in textbooks aimed for the teaching of History. As specific objectives, it was defined: a) to identify "how" the approach of the African History is proposed in the PNLD's textbooks - History - 2016 and what is its conformity with the guidelines contained in the Directives of the Law no.10,639 / 03; b) to verify how Africa and Africans are represented in the contents (written texts and images) and historical notions existing in textbooks and their respective reports, as pointed out in the PNLD Guide - History 2016; c) to verify the convergences between the records selected for analysis in the textbooks and the studies about Africa and Africans, existing in thematic studies and, d) to recognize the elements that operate in the production of textbooks and which result in a given elaboration form. The research is identified by a qualitative nature, (GAMBOA, 2003), with a bibliographic and documentary base, being theoretically based on cultural and sociological studies that allow to investigate the relations of power implied in the practices of differentiation and identification of subjects through the curriculum, school organization and educational policies. The organization and sequence of the analysis procedures of the various textual and imagery registers under study, are guided by the floating reading in search of thematic and conceptual elements, such as proposed by Minayo (2004). As major results, we highlight that, although the continuities regarding the teaching of history traditionally taught are maintained, are observed attempts of change in order to adjust to Law no. 10,623/03 and to PNLD criteria. The criticisms we raise do not have the purpose of discarding the textbook, instead, the idea is to make notes so that this material, considered by us as one of the main resources for teaching and learning of History in educational institutions, to be problematized and questioned.